Pengembangan Lampu Jalan Otomatis Berbasis Sensor Cahaya Sebagai Infrastruktur Cerdas di Desa Sukajadi Lampung - Bindar, Muhammad Abdul Mubdi; Nurhayati, Misfallah; Ashari, Ilham Firman; Tanjung, Adinda Sekar; Agustine, Verlina (LPPM Universitas Trunojoyo Madura, 2025)
Insufficient street lighting in Sukajadi Village, Central Lampung, increases accident risks and hinders economic activity. This research developed an automatic solar-powered Public Street Lighting (PJU) system using a Light Dependent Resistor (LDR) sensor. Stages included survey, design, assembly, testing, installation, socialization, and monitoring. Consequently, an automatic street light was successfully installed at the Sukajadi-Wates Village border, operating automatically with an LDR sensor and solar power. Success was marked by improved lighting, renewable energy use, proper technology function, and community satisfaction. Further development and routine maintenance are recommended for this smart infrastructure's sustainability.